Rekonstruksi Makna Pernikahan Dini Melalui Penyuluhan Berbasis Konstruksi Sosial - Adinda Luthfia Risky; Ananda Nasywaa NIsriina; Diana Febrianty Putri; Fitria Hardiyanti; Karina Dewi Julianida Firman; Siti Fatimah; Yulianti Noor Islami; Yoga Prima Putra (Jurnal Ksatria : Jurnal Pengabdian Kepada Masyarakat, 2024)
Low public awareness of the waste problem is the main thing that results in the continued increase in piles of waste in the environment. The accumulation of waste that is not managed properly can certainly have a negative impact on the environment. Apart from causing environmental pollution, the accumulation of this waste can also have a negative impact on soil and air conditions due to the methane gas produced from decomposing waste that is not properly managed. In this regard, there is a need for education and solutions to deal with these problems. Eco-enzyme is one solution that can be applied in society to overcome the waste problem. Eco-enzyme is a product that can save the environment because it is made from the fermentation of natural ingredients such as organic waste, sugar, and water, which, of course, can reduce the potential for environmental pollution due to waste that is not managed properly. Eco-enzymes can be used as natural cleaners and fertilizers, and they can even improve the condition of polluted river water and restore soil fertility. In the context of community service, eco-enzyme is not only beneficial for the environment but can also have a positive impact on the community's economy by selling eco-enzyme products to farmers and the wider community